Incidencia de la implementación de estrategias, en la aplicación del IVAP y el SPOT por los agricultores, molineros y comerciantes de arroz del Valle Jequetepeque, en el mejoramiento de la recaudación fiscal. - Ruiz Amaya, Leny Omar (2012)
The present investigation aims to determine the incidence due to the application and SPOT IVAP in rice production chain Jequetepeque valley in tax revenues, leaving the state to collect some monetary resources, which serve to develop , social and economic community to which they belong. In this thesis seeks to review and analyze all the rice production chain, from production to marketing to the consumer of it, trying to find why farmers, millers and rice traders and especially people who have nothing to do with the matter, involving ghostly order to take advantage of the situation and opt for informality, even though the state has created special tax laws led to the latter, in order to avoid that tax evasion and seek their formalization. And likewise give the agency responsible for tax collection (SUNAT) of strategies to avoid such a misapplication of the tax laws with respect to rice production chain. SUNAT has to strengthen its power to control in order to prevent funds for the state for taxes, have to end up enriching people who do not belong to the category and nor do business with it.